Sensory Motor Interventions in the Kinesthetic Development of Autistic Children: Exercise Literature Review - Ira Ocktavia Siagian; Endang Rochyadi; Budi Susetyo; Herlina Hasan (GLOBAL HEALTH SCIENCE GROUP, 2025)
Autism Spectrum Disorder (ASD) is often accompanied by impairment in motor skills and sensory processing, which impacts a child's kinesthetic development. This study aims to examine the effectiveness of sensory motor training interventions in improving the kinesthetic skills of autistic children through a meta-analysis of four national journals in 2021-2023. The four journals include direct interventions in the form of physical exercises, creative media such as batik, and educational game tools Maze Dua Sisi (MADASI). At the time of the journal search the keywords